Colchicine: A New Dawn for Preventing Complications After Heart Attack? Unveiling its Network Pharmacology and the COLD-MI Trial - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Acute myocardial infarction, or heart attack, remains a significant cause of morbidity and mortality globally. Despite substantial advancements in acute management, the residual risk of recurrent coronary events, including myocardial infarction, stroke, and heart failure, poses a substantial challenge. This persistent threat underscores the imperative for ongoing research into novel therapeutic strategies to improve patient outcomes. The recently published COLD-MI trial results has generated significant interest by highlighting the potential of colchicine, a readily available and inexpensive medication, in preventing complications after a heart attack. This report delves into the rationale behind the COLD-MI trial, scrutinizes its findings, and explores the implications in correlation with network pharmacology of colchicine for future clinical practice